Metapopulation Dynamics of a Burrowing Herbivore Drive Spatio-temporal Dynamics of Riparian Plant Communities - Bryce, Rosalind; van der Wal, René; Mitchell, Ruth; Lambin, Xavier (Ecosystems (New York), 2013)
Animals can modify their environment by consumptive and physical activities such as herbivory and soil disturbance. Engineering species may create structures that long outlive them and have lasting impacts on local communities of plants and animals. Water voles, Arvicola amphibious, are rodents that visibly impact riparian plant communities by grazing on surface and root vegetation and excavating long-lasting burrow systems. This species has a metapopulation structure and occurs across patches which are subject to frequent extinction and colonization events, causing spatially heterogeneous disturbances across the landscape. Using a chronosequence of water vole occupancy in the Highlands of Scotland, we show that heterogeneity in plant community composition and structure—both within and between colony patches—was related to cumulative measures of past physical impact: burrow density and time since a patch was last occupied by voles, rather than to current indices of vole occupancy. In our sample of 107 patches monitored over 5 years, no fewer than 31 unique patch occupancy histories were found, each with potentially subtle differences in the accumulated influence of water vole herbivory and engineering. As a result, a patchwork of different plant successional stages occurs across the riparian landscape which is both created and maintained by water vole extinction-colonization dynamics. We propose that the water vole-vegetation system can be described as a metacommunity where dispersal by a higher tropic agent at the landscape scale influences the spatial dynamics of plants at the patch level.